Student guide and workbook for use with Macroeconomics - Kaufman, Roger T.; Mankiw, N. Gregory (New York: Worth, 2003)
This guide offers various ways for students to learn the material in the new edition of Macroeconomics and assess their understanding of theories and their application to reality.
rpm 30/10/13
Loans
Keywords: Macroeconomics; Macroeconomics -- Problems, Exercises